Ocena pracy nauczyciela jako formalny wyznacznik profesjonalizmu w codzienności zawodowej - Musiał, Ewa (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Everyday life is materialized in specific phenomena and activities. The larger the professionalism of professional teachers, the educational space of everyday life will be characterized by higher quality (accuracy, neatness, uniqueness). Evaluation of the teacher’s administrative team activities in the field of pedagogical supervision. It is aimed at making opinion given on the basis of widely made a diagnosis of the extent to which the teacher performs his duties. Obtaining, highly rated, the effects of the daily work of teaching, education or care as a result of the promotion of actions aimed at improving teachers’ own work contributes to the improvement of the quality of work of educational institutions.
Keywords: assessment work; professionalism professional; teacher